An investigation into the risk factors of musculoskeletal diseases and the association between chronic diseases of lifestyle in an under-resourced area of the Cape Town Metropole - Britz, Carmen (Department of Health and Rehabilitation Sciences, 2020)
Background: A recent shift in the global burden of disease from communicable to noncommunicable has shown that a third of the global burden of disease is attributable to noncommunicable disease, with the heaviest burden affecting poor communities in urban areas. Musculoskeletal disease (MSD) is the most common cause of severe chronic or persistent pain, functional limitations, and physical disability, affecting 20-50% of adults. Globally, disability due to musculoskeletal disease is estimated to have increased by 45% from 1990 to 2010 accounting for 6.8% of total years lived with disability. Research has highlighted a possible co-existence of musculoskeletal disease and chronic noncommunicable diseases of lifestyle, however, there is inadequate South African evidence regarding these inter-relationships and possible risk factors. This highlights a gap in research as management may not be appropriately targeted toward risk factors and thus may not reduce the high prevalence rates of musculoskeletal disease. Aim: The main aims of this study were firstly to determine the prevalence and patterns of acute and chronic musculoskeletal disease. The secondary aim was to explore the relationship between these factors by examining the patterns of onset of musculoskeletal disease, chronic diseases of lifestyle, and risk factors across gender and six age categories (from 18 years to 70 years and older) in patients seeking medical services at a community health centre in Cape Town, South Africa. It was hypothesised that if some conditions were found to have an earlier onset, these conditions might lay the foundation for the development of other chronic diseases of lifestyle and musculoskeletal disease. Methodology: A descriptive, cross-sectional, analytical study design was used at primary health care level at a community health centre in Cape Town, South Africa. All males and females aged 18 years and older, except those who were pregnant or unable to answer the English, Afrikaans, or isiXhosa versions of the selected questionnaires, were eligible to participate. The outcome measures were the Community Orientated Program for Control of Rheumatic Diseases (COPCORD) screening tool for musculoskeletal disease, the Brief Pain Inventory (BPI), the European Quality of Life-5 Dimensions (EQ-5D) health-related quality of life measure, the International Physical Activity Questionnaire (IPAQ), and anthropometric measures of weight, height, and waist and hip circumference. Data were collected via interview and anthropometric measurement. Responses were captured by online questionnaires on mobile devices using the mobile data collection application Magpi by DataDyne Group, LLC. Data were exported to Microsoft Office Excel spreadsheets for descriptive and inferential statistical analysis. Ethical permission was obtained from the University of Cape Town. Results: This study recruited 1115 participants, with a mean age of 48.7 ± 16.8 years. A prevalence rate of 33.6% (95% Confidence Intervals; CI: 30.1-36.5%) for acute MSD and 43.3% (CI: 40.4-46.3%) for chronic MSD was found. The number of participants reporting an overall prevalence of any MSD was 505 (45.7%; CI: 42.8-48.7%). The highest prevalence of MSD was found in females aged 40-59 years. The most common anatomical sites of chronic MSD were the knees (35.6%; CI: 31.5-39.9%), low back/pelvis (33.8%; CI: 29.8- 38.0%), shoulders (26.8%; CI: 23.1-30.9%), and hands/fingers (21.9%; CI: 18.5-25.7%). Of those with MSD, exercise was reported as the best management strategy for musculoskeletal pain (35.6% of 191 respondents; CI: 29.1-42.6%). Hypertension was found to be the most prevalent chronic disease of lifestyle (47.8%; CI: 44.8-50.7%), followed by type 2 diabetes mellitus (21.4%; CI: 19.1-23.9%), and hypercholesterolaemia (20.2%; CI: 17.9-22.6%). All chronic diseases, except chronic obstructive airway disease (COAD), increased with age, while COAD and both acute and chronic MSD peaked around the 50-59 age category and then decreased with age. Most females reported to be highly physically active (46.0%) while males reported mostly low physical activity levels (47.8%). Around the 50-59 year old age group the proportion of participants with a ‘high’ physical activity level decreased while that of participants with a ‘low’ physical activity level increased at the same age group. A higher proportion of those without MSD reported ‘high’ levels of physical activity (41% compared to 32%). In the 30-39 and 40-49 age groups, low levels of physical activity were associated with chronic MSD (70.6% compared to 37.5% of those. with high levels; Chi-Square=13.833; df=2; p=0.001). Body mass index (BMI) category was found to be associated with MSD (p< 0.001) with 73% of those with MSD being overweight or obese and 27% being extremely obese. There were significant differences in BMI between those with and without hypertension (p< 0.001), hypercholesterolaemia (p <0.001), and type 2 diabetes mellitus (p< 0.001). A trend of increasing obesity, high waisthip ratio and low levels of physical activity with age was observed. In smokers, being 30 years of age or older was associated with an increased risk of MSD (42% compared to 21.1%). Gender emerged as a risk factor in the 40-49 and 50-59 age categories with 76.2% of females in these categories reporting chronic MSD compared to 45.1% of the males. However, no risk factor seemed to track the plot of MSD. Age emerged as having the highest association with chronic MSD (Chi-Square=136.6; p< 0.001). Conclusions: Bivariate associations of musculoskeletal disease and chronic diseases of lifestyle were detected because they all become more prevalent with age. The comorbidity of musculoskeletal disease and chronic disease of lifestyle appeared to almost entirely be due to the aging process, rather than the mutual influence that musculoskeletal disease and chronic diseases of lifestyle may have. Low levels of physical activity were only associated with musculoskeletal disease among those in the 30-49 age categories. As previous evidence has shown that increased levels of physical activity can reduce pain in chronic or persistent musculoskeletal disease, a window of opportunity is suggested where increasing physical activity levels in the 30-49 age group may result in a decrease in the prevalence of musculoskeletal disease in the older age group. The only factor that emerged as being predictive in the group with the highest prevalence of musculoskeletal disease, the 40-59 age categories, was gender. Although gender is clearly not modifiable, this finding should inform the development of culturally appropriate intervention strategies. Implications: Although it was not possible to detect any evidence supporting causation, the co-existence of chronic musculoskeletal disease, chronic diseases of lifestyle, and risk factors highlights the need for holistic care to address the multiple problems experienced by adults, specifically as age progresses. The impact of chronic musculoskeletal disease is large, both in terms of prevalence and impact on health-related quality of life. The management of chronic musculoskeletal disease should thus focus on the most effective and affordable intervention strategies and healthcare systems and coherent policies for dealing with this condition should be developed. This management should not only be based on a pharmacological model but on biopsychosocial integration emphasising self management.